Hadith Studies in Eastern Indonesia: Futurology Analysis on Hadith Sciences Department in Islamic Higher Education - Gaffar, Abdul; Akbar, Akbar (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2024)
Albeit research related to the development of hadith studies in Indonesia has been employed, little empirical research reports on the future of hadith studies, especially in Eastern Indonesia, which has had its own phenomenon in scientific development. The study focuses on the Hadith Science Study Program which is held at two PTKINs in the Sulawesi region as a representation of Eastern Indonesia in hadith education in higher education whose development is slow compared to hadith studies in other regions in Indonesia. This qualitative research utilizes observation and interview data analyzed futuristically with a predictive approach to map current trends and predict future developments, as well as to outline necessary actions to face the future in the context of hadith studies development in Eastern Indonesia. The research findings indicate that formal hadith education will lose its significance in religious education at Islamic higher education institutions in Eastern Indonesia. Trends from the analysis of historical, political-policy, and educational culture indicate a low prospect for the development of hadith studies in Eastern Indonesia. Developing interest and awareness in hadith studies through the implementation of an integrated scientific strategy is crucial. This research also emphasizes the importance of strengthening national and international collaboration among students and lecturers, focusing on the digitization of hadith studies. Furthermore, Islamic higher education institutions must engage in promoting hadith learning at all educational levels, both formal and non-formal.